Potential Application of Natural and Modified Orange Peel as an Eco‒friendly Adsorbent for Methylene Blue Dye - A. Salman , Taghried; I. Ali, Mayasa (Iraqi Journal of Science, 2023)
In this paper, the adsorption behavior of Methylene blue dye by orange peels, which was chemically modified with sodium hydroxide, has been investigated. Physical and chemical properties of both sorbents under study were determined using Fourier Transform Infrared Spectrophotometer (FTIR), Scanning Electron Microscope (SEM), Atomic Force Microscope (AFM) and Brunauer, Emmett and Teller (BET) specific surface-area measurement techniques. Effect of the solution‒pH, adsorbent dose, adsorption time, temperature and initial methylene blue concentration were studied in batch experiments. The experimental data were fitted into the following kinetic models: pseudo-first order, pseudo-second order, and the intraparticle diffusion model. It was observed that pseudo-second order kinetic model described the adsorption process with high coefficients correlation (R2) better than any other kinetic models. The kinetic investigations also reveal that intraparticle diffusion mechanism was operative equilibrium isotherms, for the adsorption of MB on OP and Sodium orange peels were analyzed considering the Langmuir, Freundlich and Temkin isotherms models. The Freundlich isotherm provided the best fit for MB dye adsorption onto OP and SOP, and the maximum adsorption capacity was found to be 14.164 mg.g-1for OP and 18.282 mg.g-1for SOP, respectively. Different thermodynamic parameters, namely Gibb’s free energy, enthalpy and entropy of the adsorption process have also been evaluated, and the data obtained indicated that the adsorption process of dye onto OP and SOP surfaces was exothermic in nature. The results show additional chemical modification of the adsorbent by NaOH leads to increased adsorption capacity.